Art museums as a source of well-being for people with dementia: an experience in the Prado Museum. Issue 3 (2nd September 2018) - Belver, Manuel H.; Ullán, Ana M.; Avila, Noemi; Moreno, Carmen; Hernández, Clara
Abstract: Background: Several studies have revealed the positive effects that cultural activities may have on people with dementia (PWD). The goal of this study was to describe the design, development and evaluation of a programme of artistic education activities for these people based on visits to the Prado Museum. Methods: 12 people participated for two months in a program of artistic activities consisting of visits to the Prado. To determine the participants' response to the programme, information was gathered through participant observation. Results: During the development of the program, the participant's reactions of interest, engagement and satisfaction, as well as a positive effect on mood and social relations, were observed. Conclusion: The cognitive difficulties did not deter them from participating in the program, which had positive effects on the participants. It was concluded that the museum can be an important resource for the promotion of PWDs' well-being and social inclusion.